Factors associated with acute watery diarrhea among children aged 0–59 months in Obongi District, Uganda, April 2022: A case–control study - Juniour Nsubuga, Edirisa; Kirabo, Jireh; Kwiringira, Andrew; Andaku, Linus; Magona Nerima, Saharu; Nsubuga, Fred; Nakazzi, Rashida; Kwesiga, Benon; Bulage, Lilian; Kadobera, Daniel; Edward Okello, Paul; Riolexus Ario, Alex (Elsevier Ltd, 2024)
Abstract • Poor caregiver hand hygiene linked to acute watery diarrhea in children. • Source of water in a home was associated with acute watery diarrhea in children. • Rotavirus vaccination only, not enough to prevent acute watery diarrhea in children. • Educate communities on handwashing at critical times, using clean water & soap. • Stresses need for treated pipped/tap water in every household.
Keywords: Papillomavirus vaccines Papillomavirus Infections/prevention & control Vaccination Provider communication Primary prevention